Site Formation Processes and Depositional Environment of a Fine‐Grained Alluvial Floodplain at La Playa Archaeology Site, Sonora, Mexico. Issue 2 (28th November 2016) - Schott, Amy M.
Abstract : Located on a floodplain of the Rio Boquillas, the site of La Playa contains a principal occupation during the Early Agricultural period, 1200 B.C.–A.D. 50 (3150–1900 cal. yr B.P.). Local complexity in geomorphic features and extensive historic dissection of the floodplain have resulted in limited understanding of the site's alluvial history, which hampers understanding of archaeological features and an extensive canal system. This study reconstructs the site formation processes of the floodplain before, during, and after occupation by comparing soils and sediments from the Los Montículos area near the channel with those of more distant areas of the site. Sediments on the floodplain were deposited by low‐energy overbank deposition from ca . 4300 to 1600 cal. yr B.P., resulting in stratified deposits with weak soil development nearer to the channel, and more strongly developed soils farther from the channel. Low‐energy deposition of fine‐grained sediments was possible due to the stable location of the river channel during the Holocene, creating an attractive place for canal agriculture. Sometime after the Early Agricultural period, higher‐energy flows resulted in deposition of sandier sediments and multiple episodes of erosion and deposition in Los Montículos, where nearly all cultural material is now in a reworked context.